Person Job Fit, Job Crafting, Dan Work Engagement Dan Pengaruhnya Terhadap Organizational Citizenship Behavior Pada Perusahaan Daerah Air Minum Surya Sembada Kota Surabaya - Arlisa Indriawati (Jurnal Manajemen dan Ekonomi Kreatif, 2024)
This research is intended to determine the influence of Person Job Fit, Job Crafting and Work Engagement on Organizational Citizenship Behavior in Employees of Regional Drinking Water Company (PDAM) Surya Sembada Surabaya City by involving 65 employees of PDAM Surya Sembada Surabaya City as respondents in this research. The research results prove that Person Job Fit has a positive and significant effect on Organizational Citizenship Behavior. This means that if the employees have the appropriate Person Job Fit, a sense of mutual help behavior will be created between employees. Job Crafting has a positive and significant effect on Organizational Citizenship Behavior. This means that if employees apply Job Crafting, it will increase Organizational Citizenship Behavior. Work Engagement has a positive and significant effect on Organizational Citizenship Behavior. This means that if employees feel work engagement, it will also increase Organizational Citizenship Behavior. Simultaneously Person Job Fit, Job Crafting and Work Engagement have a positive and significant effect on Organizational Citizenship Behavior with coefficient of determination of 0,96 or 96%, this indicates that the Organizational Citizenship Behavior variable can be explained by the Person Job Fit, Job Crafting and Work Engagement variables by 96%.